Kinematic analysis of sensorimotor control during the craniocervical flexion movement in patients with neck pain and asymptomatic individuals: a cross-sectional study - Bocos-Corredor, Elena; Moggioli, Filippo; Pérez-Fernández, Tomás; Armijo-Olivo, Susan; Sánchez, Cristina; Cuenca-Zaldívar, Juan Nicolás; Fernández-Carnero, Josué; Martín-Pintado-Zugasti, Aitor (Journal of neuroengineering and rehabilitation, 2023)
Patients with craniocervical pain have shown reduced performance in the craniocervical flexion test (CCFT). However, there is limited evidence of other possible kinematic alterations not assessed in the context of the CCFT. Previous studies on other functional or planar movements have reported alterations in sensorimotor control (e.g., range of motion [ROM], velocity, or smoothness) in subjects with neck pain. The objective of this study was to explore the association between sensorimotor control variables associated with craniocervical flexion movement and different characteristics related to pain, age, disability, and fear of movement in individuals with non-traumatic chronic neck pain and asymptomatic controls. This was an observational, cross-sectional study in patients with non-traumatic neck pain and asymptomatic participants. Regression models were used to assess whether descriptive characteristics of the sample, including: (a) age, (b) intensity of pain, (c) neck disability, (d) chronicity of pain, and (e) fear of movement could explain sensorimotor control variables such as ROM, velocity, jerk, head repositioning accuracy, and conjunct motion. All these variables were recorded by means of light inertial measurement unit sensors during the performance of three maximal repetitions of full range craniocervical flexion in the supine position. A total of 211 individuals were screened and 192 participants finished the protocol and were included in the analyses. Participants had an average age of 34.55 ± 13.93 years and included 124 patients with non-traumatic neck pain and 68 asymptomatic subjects. Kinesiophobia partially explained lower craniocervical flexion ROM (p = .01) and lower peak velocity in flexion (P < .001). Age partially explained increased craniocervical extension ROM (P < .001) and lower peak velocity in flexion (P = .03). Chronicity partially explained increased lateral flexion conjunct motion (P = .008). All models showed low values of explained variance (< 32%) and low absolute values of regression coefficients. This study did not find a clear relationship between population characteristics and sensorimotor control variables associated with the craniocervical flexion movement. Kinesiophobia might have some association with reduced ROM in craniocervical flexion, but further research in this field is needed in large samples of patients with higher levels of kinesiophobia pain or disability.